2017
DOI: 10.1111/sdi.12588
|View full text |Cite
|
Sign up to set email alerts
|

Twice‐Weekly Hemodialysis in China: Can It Be A Better Option for Initiation or Maintenance Dialysis Therapy?

Abstract: Cumulative evidence indicates it may be worthwhile revisiting the twice-weekly hemodialysis (HD) regimen as a valid option for individualized or incremental treatments for selected patients with end-stage renal disease. In this article, we will review the current evidences on the potential pros and cons of twice-weekly HD compared to thrice-weekly HD including China’s experience in the practice of twice-weekly HD. A prudent patient selection and close dialysis adequacy monitoring might be necessary for this me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…Patients with long interdialytic intervals may be more prone to larger interdialytic weight gain, and intradialytic hypotension increases due to larger fluid removal . In addition, the adequacy of dialysis is another consideration when starting incremental HD . Our study showed that the clinical condition of patients on incremental HD was similar to that of patients on conventional HD, except that they had higher renal function at baseline.…”
Section: Discussionmentioning
confidence: 55%
“…Patients with long interdialytic intervals may be more prone to larger interdialytic weight gain, and intradialytic hypotension increases due to larger fluid removal . In addition, the adequacy of dialysis is another consideration when starting incremental HD . Our study showed that the clinical condition of patients on incremental HD was similar to that of patients on conventional HD, except that they had higher renal function at baseline.…”
Section: Discussionmentioning
confidence: 55%
“…In a cross‐sectional report from China in 2013, 26% of HD patients were dialyzing twice weekly . Overall, about one‐fourth of the contemporary dialysis population in China reportedly dialyzes weekly twice and this practice is also very common, although not as well reported, in other South Asian countries …”
Section: Discussionmentioning
confidence: 99%
“…10 Overall, about onefourth of the contemporary dialysis population in China reportedly dialyzes weekly twice and this practice is also very common, although not as well reported, in other South Asian countries. 3,11 In western countries, twice weekly dialysis is much less common. Only 4% of subjects in a USRDS study from 1999 were dialysed twice weekly, and tended to be older, smaller and with lower serum creatinine concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…This paradigm shift has also led to renewed interest in “late” and, whenever possible, incremental dialysis initiation, in which, as occurs in peritoneal dialysis, hemodialysis is prescribed with a progressive increase in the number and duration of sessions to try to minimize “dialysis shock” and preserve residual renal function [ 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Tolerance Beyond Depurationmentioning
confidence: 99%
“…At dialysis start, incremental policies allow us to test for tolerance, starting with once- or twice-weekly sessions of 2–3 h, and progressively increasing frequency or duration according to need for increasing depuration or ultrafiltration and to tolerance [ 37 , 38 , 39 , 40 , 41 , 123 , 124 , 125 , 126 , 127 , 128 , 129 ] ( Figure 6 ).…”
Section: Poor Nutritional Status Poor Clinical Condition High MImentioning
confidence: 99%